Etika Berkomunikasi di dalam Al-Qur’an - Hikmatullah Jamud (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2019)
Humans are social creatures who always communicate with each other even with other creatures and the natural surroundings, in communicating humans are given the potential of speaking intelligence, God says. That is, (God) the Most Gracious, Who has taught the Koran, He created man. Teaches him to speak (Q.S, Ar-Rahman: 1-4). Given the different objects of communication the Koran has taught methods of speech that are adapted to the object, for example by using the right words (QS, 33:70), words that touch the heart (QS, 4:63) good words ( QS, 4:05) and others. It is in accordance with the words of the Prophet, speak with them according to their ability